2019
DOI: 10.1121/1.5126941
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and identification of lexical tones and consonants in Mandarin-speaking children using cochlear implants

Abstract: Mandarin-speaking adults using cochlear implants (CI) experience more difficulties in perceiving lexical tones than consonants. This problem may result from the fact that CIs provide relatively sufficient temporal envelope information for consonant perception in quiet environments, but do not convey the fine spectro-temporal information considered to be necessary for accurate pitch perception. Another possibility is that Mandarin speakers with post-lingual hearing loss have developed languagespecific use of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…were not reported. Cabrera et al [10] examined discrimination between manner and place of articulation contrasts in quiet for a group of children using CIs and a group of children with NH. The results showed children with CIs had significantly more difficulty in discriminating consonant place contrasts compared to other contrasts.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…were not reported. Cabrera et al [10] examined discrimination between manner and place of articulation contrasts in quiet for a group of children using CIs and a group of children with NH. The results showed children with CIs had significantly more difficulty in discriminating consonant place contrasts compared to other contrasts.…”
Section: Plos Onementioning
confidence: 99%
“…No significant difference was observed between children with NH and HL when consonants were contrasted by voicing and aspiration, although results from individual consonant contrasts were not reported. Cabrera et al [ 10 ] examined discrimination between manner and place of articulation contrasts in quiet for a group of children using CIs and a group of children with NH. The results showed children with CIs had significantly more difficulty in discriminating consonant place contrasts compared to other contrasts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on tone recognition in Cantonese-speaking children with CIs found that such children have a great difficulty with lexical tone perception (Ciocca et al 2002; Lee et al 2002). Mandarin-speaking children with CIs had marked deficits in tone recognition (Mao & Xu 2017; Peng et al 2017; Cabrera et al 2019; Hong et al 2019) and in consonant recognition (Cabrera et al 2019; Hong et al 2019). Studies on tone production in Mandarin-speaking children with CIs showed that the tone patterns were produced imperfectly by children with CIs (Peng et al 2004; Xu et al 2004; Tang et al 2019), but early implantation helped them to develop more normal lexical tone categories (Tang et al 2019).…”
Section: Introductionmentioning
confidence: 99%